2019
DOI: 10.29327/24816.4.1-11
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of inflammation and matrix metalloproteinase expression in dental pulp induced by luting agents in dogs

Abstract: Palavras-chave: Agentes Cimentantes. Cimento Resinoso. Cimento de Ionômero de Vidro. Capeamento Pulpar Indireto. Metaloproteinases de Matriz. RESUMOObjetivo: Avaliar a resposta tecidual inflamatória e a expressão de metaloproteinase de matriz (MMP) -2 e -9 no complexo polpa-dentina em resposta aos cimentos RelyX TM Unicem (RU) e Ketac Cem TM Easymix (KC). Métodos: Cavidades classe V foram preparadas em 56 dentes de seis cães, e capeamento pulpar indireto foi realizado com cimento de RU (n = 20), KC (n = 20), ó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…39 In a recent animal experiment, researchers concluded that RU was safe to use in deep cavities, although it led to a minor reduction in odontoblast cells with a higher ratio of mononuclear cells. 17 Also, Alvarez et al 21 reported that SARCs could delay reparative dentin formation in their investigation using MDPC-23 odontoblast-like cells. Considering the previous findings and induced apoptosis ratio by RU, it could be proposed that the cytotoxicity of this material mainly occurs through necrotic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In a recent animal experiment, researchers concluded that RU was safe to use in deep cavities, although it led to a minor reduction in odontoblast cells with a higher ratio of mononuclear cells. 17 Also, Alvarez et al 21 reported that SARCs could delay reparative dentin formation in their investigation using MDPC-23 odontoblast-like cells. Considering the previous findings and induced apoptosis ratio by RU, it could be proposed that the cytotoxicity of this material mainly occurs through necrotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all its ease of use and popularity, there are reservations about the biocompatibility of SARCs recently. [17][18][19][20][21] Thus far, the cytotoxicity of calcium-and fluoride-releasing contemporary SARCs has not been studied. Therefore, the aim of this in vitro study was to investigate the effects of four different SARCs on cell cultures using various testing methods: (1) extract testing, (2) cell culture inserts, and (3) dentin barrier testing.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos prévios demonstraram também que os adesivos dentinários autocondicionantes são capazes de aumentar a atividade colagenolítica no complexo dentino-pulpar, via ativação de MMPs in vitro 72,117,49 , enquanto o cimento de óxido de zinco e eugenol inibiu a expressão das MMPs ex vivo 105 . Os agentes cimentantes Ketac Cem e Rely-X Unicem são materiais que induzem a produção de MMP-2 e -9 quando implantados no tecido conjuntivo de camundogos 98 , porém compatíveis e não modulam a produção dessas enzimas no tecido pulpar, ao serem utilizados em cavidades profundas 97 .…”
Section: Mmps No Complexo Dentino-pulparunclassified
“…Após a anestesia e eutanásia em câmara de Rossi et al 2007;De Rossi et al 2008;Paula-Silva et al 2009b). Para realização das medidas foi utilizado parâmetros como espessura e área de dentina neoformada e a resposta inflamatória local, conforme descrito previamente por nosso grupo de pesquisa (Silva et al, 2007;Silva et al, 2017;Queiroz et al, 2019). O espaço do ligamento periodontal ou a lesão periapical foi medido para análise quantitativa, de acordo com parâmetros descritos anteriormente (De Rossi et al 2008, Paula-Silva et al 2009cPetean et al, 2021).…”
Section: Processamento Histotécnico Das Amostrasunclassified